Prevalence of Tuberculin Reactivity and Risk Factors for the Development of Active Tuberculosis Upon Admission to a Nursing Home - Vega Torres, Rafael A.; Conde, José G.; Diaz, Miriam (Puerto Rico Health Sciences Journal, 2025)
see manuscript